A PRISMA-based Review of Taoist Cultural Heritage and the Development of a Heritage and Strategy Matching Guide - Kamarudin, Khairul Manami; MA, Tiansu (Journal of Social Sciences and Humanities, 2026)
At present, the research on Taoist cultural heritage has not been well integrated. Lack of tangible and intangible systematic connections. To fill this gap, this study aims to conduct the first structured review of Taoist cultural heritage research published between 2010 and 2024. Systematically collect relevant research through the main academic databases and use the PRISMA guidelines for content analysis. The analysis divides the heritage into two categories: tangible (such as painting, architecture) and intangible (such as music, medicine, martial arts, philosophy), and explores the conservation strategies adopted in previous studies. Based on this result, the study develops the “Heritage and Strategy Matching Guide”, which connects five key strategies: documentation, quantitative experimental analysis, scientific and technical analysis, field investigation, and cultural integration with specific heritage categories. Cross-examination of existing case studies shows the practical relevance of the guide and its potential for wider application. The results indicate underutilized strategies and uneven research coverage, especially regarding intangible heritage. This study provides a systematic foundation for further research, promotes multidisciplinary and cross-cultural opinions, and provides beneficial suggestions for the conservation and sustainable development of Taoist heritage.